Dual effect of chemical modification and polymer precoating of flax fibers on the properties of short flax fiber/poly(lactic acid) composites. Issue 48 (14th July 2015) - Kodal, Mehmet; Topuk, Zeynep Demir; Ozkoc, Guralp; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT Polymer precoated and chemically modified short flax fiber (SFF)/poly(lactic acid) (PLA) composites were successfully produced. The main focus of this study was to investigate the effects of the combinatorial use of chemical modification methods of flax fiber, such as alkaline treatment and silane coupling agents, together with polymer precoating as the film former on the physical and mechanical properties for PLA/SFF composites. The chemically modified flax fibers were characterized by X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and scanning electron microscopy. It was revealed from XRD analysis that alkaline treatment resulted in change in the cellulose I structure to the cellulose II structure because of the removal of the cementing non‐cellulosic components. The XPS analysis showed that the silane groups were successfully bonded to the surface of the flax fiber. As the film‐former application, PLA was coated on the surface of alkaline or silane‐treated flax fiber surfaces via a solution dipping process. The SFF content was kept constant at 25 wt % in the composites that were prepared by means of a 15 mL Xplore Instruments twin‐screw compounder. After melt processing, the positive effect of the sizing application on both the alkaline‐ and silane‐treated SFF was observed from the enhanced fiber length distribution. The mechanical properties were examined by means of tensile and impact tests and dynamic mechanical analysis. In addition, the thermal properties obtained from differential scanning calorimetry were discussed as a function of the fiber treatment method. The hydrolysis rate was determined by a weight loss test in a phosphate buffer solution. The results showed that in addition to the positive single influence of the silane coupling agent, the synergetic effect of the film former (i.e., precoated polymer) and silane treatment was observed to improve the performance of the composites. The hydrolysis rate of the polymer‐coated flax‐based composites was lower than that of uncoated flax fiber composites. In addition, polymer‐coated flax fibers could be easily processed like conventional chopped short‐glass‐fiber composites. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42564.